The Peculiarities of the Perception and Understanding of Sonnets Written by W. Shakespeare by the Students of the Faculty of Foreign Languages - Наталія Михальчук; Ольга Кришевич (Психолінгвістика, 2019)
The purpose of the article is to analyze the peculiarities of the perception and understanding of Sonnets written by W. Shakespeare by the students of the Faculty of Foreign Languages.